Stress reactions in patients with schizophrenia spectrum disorders and a complex approach to their treatment - Pyliagina, Галина; Mykhaylov, Борис; Grinevich, Євгенія (Psychosomatic Medicine and General Practice, 2023)
The psychotraumatic factors that occurred during the war of 2022-2023 significantly affect on the onset and dynamics of schizophrenia spectrum disorders (SSD). Objective. To study the relationship between the influence of stress factors in patients with SSD with the dynamics of exacerbation of psychopathological symptoms and to create complex of treatment and rehabilitation (CTR) for these patients. Methods and materials. There was psychopathological examination of 68 patients with different types of SSD who experienced severe stress during the war and assessed the clinical features of theire psychotic state, and the content of stress factors. Results. In the research the largest number were patients with schizophrenia (Sch, 42.6% of cases), most often with paranoid form with progressive paroxysmal course, as well as patients with acute and transient psychotic disorders (APD), schizoaffective disorder (SchAD) and schizotypal disorder (StD). There were diagnosed affective and delusional symptoms (54.4% of cases) most often as the leading psychopathological reaction to the psychotraumatic stress effects in patients with SSD. Only patients with Sch had the highest incidence of hallucinatory-paranoid syndrome (71.4% of cases). The onset or relapse of a psychotic episode among patients with SSD developed as a result of a significant impact of stress factors with different content, but related to the war in all cases. The most frequent of these were difficulties during evacuation, which caused increasing in family conflicts, especially in patients with Sch and StD. It was found the stressful media impact caused an exacerbation of psychotic symptoms in one third of patients with Sch and StD. There was essential psychotraumatic impact to patients with SSD as of the repeated bombing; the death of relatives; fears experienced during the occupation; inability to continue treatment; and psychotraumatic circumstances associated with the loss of work or no money to live. The CTR for patients with SSD who have been significantly affected by stress based on the analysis of the relationship between nosology, clinical symptoms and stress factors. The aim of the CTR is effective treatment of a psychotic episode or reactive psychotic state, should be steady and consist of the following stages: diagnostic; emergency, outpatient and/or inpatient care; psycho-rehabilitation, as well as support and psychoprophylaxis. Its structure should combine the use of psychopharmacotherapy with psychotherapy (psychocorrection) and psychoeducation, followed support of the patient at the stage of remission.